Teacher education for basic education and art teaching: possible paths (Olhar de Professor, 2021)
Thinking about the possibilities of teaching art in education has been the subject of discussions in teacher training courses. In this sense, this report aims to bring reflections on the training of teachers to work with art and movement, on children's languages expressed by different expressive modalities, bringing propositions for pedagogical practice in different contexts, through playful activities for Basic Education. It aims to answer the following questions: how does the child come into contact with Art? What are the possibilities that the school can provide to children in Basic Education? Where to start? The results of these experiences reveal the importance of the teacher having a cultural repertoire capable of offering, encouraging and stimulating children in their learning processes in Art. It is concluded that a teacher with a rich education, and with a good artistic and cultural repertoire, will be able to give answers and share meaningful experiences in line with the interests of children.
Keywords: Basic education.; Teacher training; Art teaching.